871 Liver Transplant for Colorectal Liver Metastases: A Systematic Review and Meta-Analysis of Proportions. (12th October 2021) - Varley, R; Tarazi, M; Davé, M; Mobarak, S; Stott, M; Baltatzis, M; Satyadas, T
Abstract: Introduction: Colorectal liver metastases were historically considered a contraindication to liver transplantation, but dismal outcomes for those with metastatic colorectal cancer and advancements in liver transplantation (LT) have led to a renewed interest in the topic. We aim to compare the current evidence for liver transplantation for non-resectable colorectal liver metastases (NRCLM) with the current standard treatment of palliative chemotherapy reported in literature – 5-year survival rate <10%. Method: A systematic review and meta-analysis of proportions was conducted following screening of MEDLINE, EMBASE, SCOPUS and CENTRAL for studies reporting liver transplantation for colorectal liver metastases. Post-operative outcomes measured included 1-, 3- and 5-year survival, overall survival, disease-free survival, and complication rates. Results: Three non-randomised studies met the inclusion criteria, reporting a total of 48 patients receiving LT for NRCLM. Survival at 1-, 3- and 5-years was 83.3-100%, 58.3-80% and 50-80% respectively with no significant difference detected (p = 0.22, p = 0.48, p = 0.26). Disease free survival was 35-56% with the most common site of recurrence being lung. Thirteen out of fourteen deaths were due to disease recurrence. Conclusions: Although current evidence suggests a survival benefit conferred by LT in NRCLM compared to palliative chemotherapy, the ethical implications of organ availability and allocation demand rigorous justification. Eight registered clinical trials will report on 300 more patients undergoing LT for NRCLM over the next 10 years: concomitant improvements in the management of patients following liver resection and of palliative chemotherapy regimens is paramount.